Analysis Of Merchandise Inventory Audit In Retail Companies - Umam, Danang Choirul; Anthoni, Lukman; Yusuf, Yusuf (Journal of Economics and Business (JECOMBI), 2024)
This study aims to analyze the operational audit of merchandise inventory in retail companies. The methods used include interviews, observations, and documentation to collect relevant data related to procedures for receiving, selling, and checking merchandise inventory. The results of the study indicate discrepancies between recorded data and physical stock, caused by errors in record-keeping, oversight in inspections, and lack of supervision. Although technology such as barcode scanners has been implemented, issues like inaccurate data entry and insufficient employee training remain challenges. Investigative audits revealed that measures such as CCTV review and interviews are effective in identifying root causes, but unfair accountability policies can lower employee motivation. This study recommends improving training, supervision, and data-driven policies to minimize stock discrepancies and enhance the operational efficiency of retail companies. These findings contribute to better and more sustainable inventory management.